The Role of Cultural Context in Language Acquisition: Strategies for Effective Language Teaching in Higher Education - Burhanuddin, Burhanuddin; Nasution, Fauziah; Harahap, Tinur Rahmawati; Harahap, Adek Nilasari; Nasution, Eni Sumanti (International Journal of Educational Research Excellence, 2025)
Language acquisition is a complex process deeply influenced by cultural context, which shapes learners' cognitive frameworks, motivation, and communicative competence. This study investigates the critical role of culture in language learning and proposes pedagogical strategies to enhance language instruction in higher education. By integrating cultural elements into curricula, educators can foster deeper linguistic proficiency and intercultural awareness, preparing students for global communication. A mixed-methods approach was employed, combining an extensive literature review, classroom observations, and surveys involving university-level language instructors (N=50) and students (N=100). Findings reveal that culturally responsive teaching methods—such as the use of authentic materials, intercultural exchange programs, and learner-centered approaches that leverage students' cultural backgrounds—significantly improve language acquisition outcomes. The study concludes with practical recommendations for educators to design more inclusive and effective language programs that align with contemporary educational demands.